2015
DOI: 10.3340/jkns.2015.58.6.508
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Resveratrol on Acute Brain Ischemia Reperfusion Injury by Measuring Annexin V, p53, Bcl-2 Levels in Rats

Abstract: BackgroundCerebral ischemia is as a result of insufficient cerebral blood flow for cerebral metabolic functions. Resveratrol is a natural phytoalexin that can be extracted from grape's skin and had potent role in treating the cerebral ischemia. Apoptosis, a genetically programmed cellular event which occurs after ischemia and leads to biochemical and morphological changes in cells. There are some useful markers for apoptosis like Bcl-2, bax, and p53. The last reports, researchers verify the apoptosis with earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…Resveratrol, a stilbene formed in many plants in response to various stressors, elicits multiple beneficial effects including anti-oxidative, anti-apoptotic and anti-inflammatory properties in dozens of diseases (28). Particularly, resveratrol was shown to have therapeutic properties in neuronal following ischemia reperfusion injury (29,30). Resveratrol post-treatment protects against neonatal brain injury after hypoxia-ischemia (20).…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol, a stilbene formed in many plants in response to various stressors, elicits multiple beneficial effects including anti-oxidative, anti-apoptotic and anti-inflammatory properties in dozens of diseases (28). Particularly, resveratrol was shown to have therapeutic properties in neuronal following ischemia reperfusion injury (29,30). Resveratrol post-treatment protects against neonatal brain injury after hypoxia-ischemia (20).…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol (3,5,4 0 -trihydroxy-trans-stilbene) is a plantbased phytoalexin with antioxidant, anti-inflammatory, antidiabetic, and anti-aging properties (Kizmazoglu et al 2015). This compound, together with its dimer trans-e-viniferin, may improve cognition by modulating GABA A R-induced currents (Moussa et al 2017).…”
Section: Other Gaba a R Modulatorsmentioning
confidence: 99%
“…Cerebral ischemia is a result of insufficient cerebral blood flow for cerebral metabolic functions. Reperfusion stimulates many pathological mechanisms such as leukocyte infiltration, oxidative stress, inflammation, destruction of blood-brain barrier, platelet activation, nitric oxide release, and apoptosis [19]. …”
Section: Discussionmentioning
confidence: 99%
“…They are divided on two distinct groups, anti-apoptotic members such as Bcl-2 and Bcl-Xl that prevent cell death and pro-apoptotic members like Bax and Bak [30, 31]. The animal studies of brain ischemia-reperfusion injury showed that the level of Bcl-2 was more decreased in severe brain injury [19, 32]. Like these findings from other studies, our results show that the gene expression of anti-apoptotic protein, Bcl-2 showed greater decreases in poor neurological group compared with good neurological group.…”
Section: Discussionmentioning
confidence: 99%